Anatomical constraints to C4 evolution: light harvesting capacity in the bundle sheath. Issue 2 (4th July 2016) - Bellasio, Chandra; Lundgren, Marjorie R.
Summary: In C4 photosynthesis CO2 assimilation and reduction are typically coordinated across mesophyll (M) and bundle sheath (BS) cells, respectively. This system consequently requires sufficient light to reach BS to generate enough ATP to allow ribulose‐1, 5‐bisphosphate (RuBP) regeneration in BS. Leaf anatomy influences BS light penetration and therefore constrains C4 cycle functionality. Using an absorption scattering model (coded in Excel, and freely downloadable) we simulate light penetration profiles and rates of ATP production in BS across the C3, C3 –C4 and C4 anatomical continua. We present a trade‐off for light absorption between BS pigment concentration and space allocation. C3 BS anatomy limits light absorption and benefits little from high pigment concentrations. Unpigmented BS extensions increase BS light penetration. C4 and C3 –C4 anatomies have the potential to generate sufficient ATP in the BS, whereas typical C3 anatomy does not, except some C3 taxa closely related to C4 groups. Insufficient volume of BS, relative to M, will hamper a C4 cycle via insufficient BS light absorption. Thus, BS ATP production and RuBP regeneration, coupled with increased BS investments, allow greater operational plasticity. We propose that larger BS in C3 lineages may be co–opted for C3 –C4 and C4 biochemistry requirements.